Microsurgical neck dissection for metastasizing medullary thyroid carcinoma - Buhr, Heinz J.; Kallinowski, Friedrich; Raue, Friedhelm; Frank-Raue, Karin; Herfarth, Christian (European journal of surgical oncology, 1995)
Surgery is the only accepted method for a potentially curative treatment of metastatic medullary cancer of the thyroid (MCT). Between 5/1988 and 2/94 53 patients (mean age 43, 14-65 years) were treated. A total of 24 patients underwent surgery of both sides of the neck whereas 29 patients required only one side. Six months after surgery, a profound reduction in basal serum calcitonin levels (CT) was detected in all patients. Upon pentagastrin stimulation, CT levels remained suppressed in eight patients. A pathological increase of normalized basal CT values was noted in 33 patients. In 12 patients, basal CT concentrations remained elevated after surgery. We conclude that metastatic MCT can be effectively treated by microsurgical modified radical neck dissection.
Elektronische Reproduktion der Druck-Ausgabe 13. Oktover 2004
Gesehen am 24.09.2025